A Court of Silver Flames - Book 5 - Maas, Sarah J. (New York : Bloomsbury, 2021)
"Against the sweeping backdrop of a world seared by war and plagued with uncertainty, Nesta and Cassian battle monsters from within and without as they search for acceptance-and healing-in each other's arms"--
Keywords: Fairies -- Fiction; Imaginary wars and battles -- Fiction; Magic -- Fiction; Courts and courtiers -- Fiction; Women spies -- Fiction; Man and woman relationships -- Fiction; Monsters -- Fiction; Fantasy fiction; Romance fiction